A THP-1 Cell Line-Based Exploration of Immune Responses Toward Heat-Treated BLG - Deng, Ying; Govers, Coen; Beest, Ellen ter; van Dijk, Aalt-Jan; Hettinga, Kasper; Wichers, Harry J. (Frontiers in Nutrition, 2021)
Allergen recognition and processing by antigen presenting cells is essential for the sensitization step of food allergy. Macrophages and dendritic cells are both phagocytic antigen presenting cells and play important roles in innate immune responses and signalling between the innate and adaptive immune system. To obtain a model system with a homogeneous genetic background, we derived macrophages and dendritic cells from THP-1 monocytes. The difference between macrophages and dendritic cells was clearly shown by differences in their transcription response (microarray) and protein expression levels. Their resemblance to primary cells was analysed by comparison to properties as described in literature. The uptake of β-lactoglobulin after wet-heating (60 °C in solution) by THP-1 derived macrophages was earlier reported to be significantly increased. To analyse the subsequent immune response, we incubated THP-1 derived macrophages and dendritic cells with native and differently processed β-lactoglobulin and determined the transcription and cytokine expression levels of the cells. A stronger transcriptional response was found in macrophages than in dendritic cells, while severely structurally modified β-lactoglobulin induced a more limited transcriptional response, especially when compared to native and limitedly modified β-lactoglobulin. These results show that processing is relevant for the transcriptional response towards β-lactoglobulin of innate immune cells.